Expanded Characterization of a Hemi-Body Shielded Göttingen Minipig Model of Radiation-induced Gastrointestinal Injury Incorporating Oral Dosing Procedures. Issue 1 (January 2018) - Measey, T. J.; Pouliot, M.; Wierzbicki, W.; Swanson, C.; Brown, D.; Stamatopoulos, J.; Proulx, D.; Authier, S.; Donini, O.
Abstract : Abstract: In collaboration with the Biomedical Advanced Research and Development Authority (BARDA), the authors recently conducted a pilot study in a hemi-body shielded model of radiation-induced gastrointestinal (GI) injury in Göttingen minipigs following exposure to radiation dose levels between 8–16 Gy. Herein, the impact of oral dosing procedures is assessed, as well as the specific causes of death in animals exposed to radiation doses of 14 and 16 Gy ( n = 64; 32 male, 32 female, between 6 and 8 mo of age). Oral dosing using a 2‐tablet placebo system comprised of both immediate release and enteric-coated tablets starting 24 h post-irradiation resulted in inhibited gastric emptying of the enteric-coated tablets, which were found to be retained in the stomach and/or regurgitated. This finding appears to be species-specific, as similar findings have not been reported for other large animal species (e.g., non-human primates). Mortality was primarily dictated by decreased activity, body weight loss (>35%), and/or respiratory distress, despite shielding of the lung. The cause of respiratory distress in animals that were pre-terminally euthanized varied according to the timing of death, with interstitial inflammation and extensive fibrosis observed >20 days post-irradiation. Kidney damage was also identified in most animals after day 10. Changes in the GI tract were consistent with previous studies and included collagen deposition/fibrosis. Observations of inflammatory infiltrates and interstitial inflammation/fibrosis in both shielded and unshielded organs support a strong secondary inflammatory syndrome post-irradiation. Abstract : Supplemental digital content is available in the text.